An anisotropic linear elastic boundary element formulation for masonry wall analysis - Oliveira Neto, Luttgardes de [UNESP]; John Masia, Mark; Taguti, Yzumi [UNESP]; Carlos Rigitano, Antonio [UNESP] (My University, 2013)
This work presents an application of a Boundary Element Method (BEM) formulation for anisotropic body analysis using isotropic fundamental solution. The anisotropy is considered by expressing a residual elastic tensor as the difference of the anisotropic and isotropic elastic tensors. Internal variables and cell discretization of the domain are considered. Masonry is a composite material consisting of bricks (masonry units), mortar and the bond between them and it is necessary to take account of anisotropy in this type of structure. The paper presents the formulation, the elastic tensor of the anisotropic medium properties and the algebraic procedure. Two examples are shown to validate the formulation and good agreement was obtained when comparing analytical and numerical results. Two further examples in which masonry walls were simulated, are used to demonstrate that the presented formulation shows close agreement between BE numerical results and different Finite Element (FE) models. © 2012 Elsevier Ltd.
Keywords: Anisotropy; Boundary Element Method; Isotropic fundamental solution; Masonry; Anisotropic bodies; Anisotropic medium; Discretizations; Elastic tensors; Finite element models; Fundamental solutions; Internal variables; Linear elastic; Masonry units; Masonry walls; Numerical results; Anisotropic media; Boundary element method; Masonry construction; Masonry materials; Retaining walls; Tensors; Walls (structural partitions)